Sway : a novel - Turner, Amber McRee (Disney Hyperion, 2012)
Ten-year-old Cass's attitude changes after her mother, whom she idolizes, leaves her behind, and her father who previously seemed boring and practical, takes her on a summer road trip in which he shows her the creative, magical side of himself.